RIVIEW JURNAL : EKSTRAKSI DAN KARAKTERISASI MINYAK ATSIRI BUNGA KENANGA (Cananga odorata) DAN APLIKASINYA SEBAGAI PENOLAK NYAMUK PADA LOTION DAN PARFUM - Amelia, Nabila Putri; Farras Andika Putri; Fidela Nur Izzati; Ghina Raudhatul Jannah; Hanifah Annisa; Hudia Hudia; Lili Sarnika Nuri; Fareal Pratama Putra (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this research was to characterize the essential oil of Cananga flower (Cananga odorata) extracted using vapor distilation technique and to apply it as lotion and perfume for mosquito repellent. The charaterization of the essential oil showed that the colour, odour, and diffraction index of the Cananga essential oil have meet the quality standard of Indonesian National Standard which is SNI 06-3949-1005. However, the density of the essential oil, which was of 1.034 g/mL did not meet the requirement. The results of GC-MS (Gas Chromatography – Mass Spectrometry) analysis described that there were some main components in the Cananga essential oil such as benzyl benzoate, caryophyllene, linalool and eugenol. Furthermore, examination of the effectivity of the essential oil as mosquito repellent showed that the application of the Cananga essential oil as lotion was found to be more effective than as perfume in driving out 100% mosquitoes which were at the concentration of Cananga oil of 7.5% and of 20%, respectively.